Research on enterprise crisis prevention under the network era - Chen, Yan (Đại học Kinh tế, 2016)
Enterprises will be the impact of various factors in the development process. Sometimes the unconventional factors lead to crisis. This paper examines the impact of the network era to the enterprises crisis. The research focus on using internet information filtering model to detect the crisis signals and then taking the necessary measures to prevent the outbreak of corporate crisis.